Mosques in the metropolis: incivility, caste, and contention in Europe - Becker-Topkara, Elisabeth (The University of Chicago Press, 2021)
Preface : spirit meeting stone -- The European : where doors and walls meet -- Caste, or the order of things defied -- Kaaba in papier-mâché : Şehitlik Mosque and the metropolis -- Messianic horizon : inside the East London Mosque -- Hope, interrupted : the East London Mosque and the metropolis -- Unsettled Europe : on the threshold of remembrance -- Afterword : the memory of trees.